A High-Density Genetic Linkage Map and QTL Mapping for Sex in Black Tiger Shrimp (Penaeus monodon) - Guo, Liang; Xu, Yu-Hui; Zhang, Nan; Zhou, Fa-Lin; Huang, Jian-Hua; Liu, Bao-Suo; Jiang, Shi-Gui; Zhang, Dian-Chang (Frontiers in Genetics, 2019)
The black tiger shrimp, Penaeus monodon, is important in both fishery and aquaculture and is the second-most widely cultured shrimp species in the world. However, the current strains cannot meet the market needs in various cultural environments, and the genome resources for P. monodon are still lacking. Restriction-site associated DNA sequencing (RADseq) has been widely used in genetic linkage map construction and in quantitative trait loci (QTL) mapping. We constructed a high-density genetic linkage map with RADseq in a full-sib family. This map contained 6524 single nucleotide polymorphisms (SNPs) and 2208 unique loci. The total length was 3275.4 cM, and the genetic distance was estimated to be 1.1 Mb/cM. The sex trait is a dichotomous phenotype, and the same interval was detected as a QTL using QTL mapping and genome-wide association analysis. The most significant locus explained 77.4% of the phenotype variance. The sex locus was speculated to be the same in this species based on the sequence alignments in Mozambique, India, and Hawaii populations. The constructed genetic linkage map provided a valuable resource for QTL mapping, genome assembly, and genome comparison for shrimp. The demonstrated common sex locus is a step closer to locating the underlying gene.